Knockdown of lncRNA PVT1 attenuated macrophage M1 polarization and relieved sepsis induced myocardial injury via miR-29a/HMGB1 axis. (July 2021) - Luo, Yuan-Yuan; Yang, Zhong-Qi; Lin, Xin-Feng; Zhao, Feng-Li; Tu, Hai-Tao; Wang, Ling-Jun; Wen, Min-Yong; Xian, Shao-Xiang
Abstract: Background: LncRNA PVT1 was reported to be elevated in septic myocardial tissue. The underlying mechanism by which PVT1 aggravated sepsis induced myocardial injury needs further investigation. Methods: Mice was subjected to LPS injection to mimic in vivo sepsis model. HE staining was applied to observe tissue injury. Cardiac function of mice was determined by echocardiography. Bone marrow derived macrophage (BMDM) was used to confirm the regulatory effect of PVT1 in macrophage polarization. Western blotting or qRT-PCR were performed to evaluate protein or mRNA levels, respectively. ELISA was conducted to determine cytokine levels. Interaction between PVT1 and miR-29a, miR-29a and HMGB1 were accessed by dual luciferase assay. Results: Expression of PVT1 was elevated in myocardial tissue and heart infiltrating macrophages of sepsis mice. PVT1 knockdown alleviated LPS induced myocardial injury and attenuated M1 macrophage polarization. The mechanic study suggested that PVT1 targeted miR-29a, thus elevated expression of HMGB1, which was repressed by miR-29a targeting. The effect of PVT1 on M1 macrophage polarization was dependent on targeting miR-29a. Conclusion: PVT1 promoted M1 polarization and aggravated LPS induced myocardial injury via miR-29a/HMGB1 axis.